Relieving or Aggravating the Burden: Non-Communicable Diseases (NCDs) of Electronic and Conventional Cigarette Users (Dual Users) in Indonesia - Faizal R. Moeis; Risky K. Hartono; Renny Nurhasana; Aryana Satrya; Teguh Dartanto (Tobacco Induced Diseases)
Introduction Conventional (tobacco) and e-cigarette smoking prevalence is a growing concern in Indonesia. It has worsened as e-cigarettes complement conventional cigarettes, causing dual users. Dual users of e-cigarettes and conventional cigarettes potentially cause an additional burden in terms of the health of their users.